PENDIDIKAN KARAKTER BERBASIS SIRAH NABAWIYAH - Moh. Toriqul Chaer; Azizunisak Hidayati Wahyuna (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2020)
This study seeks to synergize the education of character-based Sirah Nabawiyah. The effort to identify the education-based moral and ethical education theme in Sirah Nabawiyah synergizes with the concept of the liberation character of Paulo Freire. The purpose of education is moral education and the ability to cultivate a liberation spirit of inequality and social discrimination in the community. This study is library research, a literary search related to the thought of Freire and the concept of Sirah Nabawiyah. This research is also included in the category of historical-factual research because the one that is research is the history of one's thinking. The results of the study found: firstly, education, according to Freire, must be able to adapt to the pace of reality, to remain in the state of being. Second, the education learning of the liberation-based character Sirah Nabawiyah rests on ethical values, perceives and loves the goodness manifested in the advocacy effort of the suppression and oppression situation. Thirdly, a release-based education based on Sirah Nabawiyah should present a critical, adaptive and integrated attitude. Finally, the hope of the education-based character Sirah Nabawiyah can advocate the problem of cultural concussion by a wise and thoughtful.